A fault-tolerant approach to the control of a battery assembly system. (October 2016) - Majdzik, Paweł; Akielaszek-Witczak, Anna; Seybold, Lothar; Stetter, Ralf; Mrugalska, Beata
Abstract: The paper concerns fault-tolerant control of a real battery assembly system which is under a pilot implementation at RAFI GmbH Company (one of the leading electronic manufacturing service providers in Germany). The proposed framework is based on an interval analysis approach, which along with max-plus algebra, allows describing uncertain discrete event system such as the production one being considered in this paper. Having a mathematical system description, a model predictive control-based fault tolerant strategy is developed which can cope with both processing, transportation and mobile robot faults. In particular, it enables tolerating (up to some degree) the influence of these faults on the overall system performance. As a result, a novel robust predictive fault-tolerant strategy is developed that is applied to the advanced battery assembly system. The final part of the paper shows the implementation and experimental validation of the proposed strategy. The proposed approach is tested against single as well as simultaneous faults concerning processing, transportation and mobile robots. Abstract : Highlights: An automated battery assembly system is designed. A mathematical framework for describing uncertain production system is proposed. A robust fault-tolerant control algorithm is proposed and applied to the battery assembly system. The proposed approach is able to deal with simultaneous processing and mobile robot faults. A comprehensive experimental study was realized in order to expose the performance of the proposed approach.